The activity of mucuna deeringiana and chenopodium ambrosioides crudes extracts upon meloidogyne incognita race 3 - DIAZ, MARISA ALVES NOGUEIRA; OLIVEIRA, JOÃO SABINO DE; FERRAZ, SILAMAR; SANTOS, MARIA AMÉLIA DOS (Revista Ceres, 2015)
.